Food Bank Operation and Perceptions of Recipients on Food Surplus Redistribution in North and South Jakarta - Khairunisa Khairunisa; Sri Setiawati; Saptarining Wulan (Jurnal Penelitian Pendidikan IPA, 2023)
Food waste is one of the highest sources of waste in Indonesia. This condition is contrary to food insecurity in Indonesia, which ranks third highest in Southeast Asia. Food waste generation reduction can be made by seeking management food surplus redistribution. Currently, the redistribution of food surplus began to be carried out to reduce food waste and food insecurity. This study aimed to determine the redistribution process of food surplus in North and South Jakarta from being collected to being sent to the recipient and the perceptions and acceptance attitudes of recipients of food surplus towards the redistribution of food they receive. The method used is using a Likert Scale and interviews. Based on the research results, there are 5 stages in surplus food management: collection and preparation, storage and inspection, delivery and receipt, documentation, and re-checking. Food surplus recipients have a good perception and acceptance of the redistribution of food surplus. However, some recipients still need to gain more knowledge about the expiration date and best-before, which affects the perception and management of food donations received. The recommended efforts include maintaining positive perceptions and attitudes of the recipient and people by developing education about food and waste management from food bank programs with support by the government institution which had same agenda and already cooperated with food bank.